Biofuels in India: Trading off climate mitigation with water security goals - Singh, Vartika; Mishra, Abhijeet; Alam, Mohammad Faiz; Sulser, Timothy B.; Ringler, Claudia (International Food Policy Research Institute, 2025)
Biofuels are recognized as a renewable alternative to fossil sources of energy like petroleum or gas. Liquid biofuels, such as bioethanol and biodiesel are blended with petrol or diesel and used for road, aviation and marine transport; they are expected to account for 6% of total renewable transportation fuel use by 2030. Biofuels can not only support a country’s mitigation goals; but also reduce the need for foreign exchange and support agricultural growth.